Prevalence of Vitamin B12 Deficiency In Patients With Type II Diabetes Mellitus On Metformin - Malla, D.; Bajracharya, M.R.; Karki, B.B.; Rajouria, A.D.; Shrestha, P.S. (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
Background: Diabetes Mellitus is one of the most encountered disease in our out patient department and metformin is the first drug of choice to treat Diabetes mellitus. As metformin is one of the cheapest drug, many patients use these drug for long period of time with consultation and without consultations with doctors. Patients under long term metformin use are not aware of Vitamin B12 deficiency and its associated signs and symptoms. In Nepal due to poverty, lack of education and awareness on diabetes mellitus we doctors find much difficult to explain patients on the consequences of diseases. So I decided to do this study which could be much easier to explain patients on effect of metformin of vitamin B12 levels and the consequences life style modifications and supplement of Vitamin B12 to the patients.Methods: This is a Cross-Sectional Study done in the patients with Type 2 diabetes were selected based on inclusion and exclusion criteria. Basic biochemical investigation were sent the lab of the National academy of medical science. Serum B12 assay were done. Vitamin B12 deficiency is defined as values